Harmonic monitoring at UniMAP distributed campus - Indra, Nisja; Ismail, Daut, Prof. Dr.; Syafrudin, M.; Risnidar Chan, Bahaudin, Ir.; Surya Hardi, Amrin (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/